Antibodies for the Coat Protein of Cotton Leafroll Dwarf Virus Detect Commelina sp. as an Intermediary Host for Cotton Blue Disease - Hoffmann, Lucia Vieira; Branquinho, Amanda Alves; Barroso, Paulo Augusto Vianna; Vaslin, Maite F. S. (Frontiers in Plant Science, 2022)
The cotton blue disease, caused by the cotton leafroll dwarf virus (CLRDV), leads to dwarfism, leaf rolling, and production loss in susceptible cotton varieties. To develop an enzyme-linked immunosorbent assay (ELISA) test to detect the virus in cotton and weeds, peptides based on the coat protein were used to produce polyclonal (α-GQE, α-PRN, and α-INK) and monoclonal (α-GQE, α-PRN, and α-NKF) antibodies. All six were tested as capture antibodies, and polyclonal α-GQE and the monocle onal α-NKF were labeled with the enzyme alkaline phosphatase and used as detection antibodies for a double antibody sandwich (DAS) ELISA method, in which p-nitrophenyl phosphate was added and measured by absorbance at 405 nm. The DAS-ELISA sandwich was efficient in discriminating between healthy and diseased plant extracts. The ELISA methodology detected the virus in the weeds Commelina sp., which was confirmed by RT-PCR. The monoclonal antibodies may be used to develop other diagnostic procedures.